Review of animal responses to climate variability (Zoological Records and Reviews, 2025)
Animal responses to climate variability -- encompassing both long-term directional change and short-term inter-annualand seasonal fluctuations -- span a hierarchy of biological organisation from molecular and physiological adjustmentswithin individuals, through phenological and behavioural plasticity, to population demographic responses, distributionalshifts, and ultimately evolutionary adaptation or local extinction. Understanding the mechanisms, magnitudes, andconservation consequences of these multi-level responses is central to predicting biodiversity trajectories under projectedclimate scenarios and designing effective adaptation strategies. This review synthesises evidence from 228 primarystudies (2005-2025) examining animal responses to climate variability across European terrestrial, freshwater, andmarine ecosystems, evaluating six response domains: phenological shifts, distributional range changes, demographicrate changes, physiological stress responses, evolutionary adaptation, and multi-species interaction disruptions(phenological mismatches). European breeding bird arrival dates have advanced by a mean 5.8 +- 1.4 days per decadesince 1970 across 146 species, with highest advancement in long-distance migrants (8.4 days/decade) and lowest inshort-distance migrants (3.2 days/decade). Species range boundaries have shifted northward at a mean velocity of 16.4+- 4.8 km per decade for European vertebrates, significantly slower than projected climate velocity (42.4 km/decade),indicating that range shifts are lagging climate change with potential debt accumulation. Phenological mismatchesbetween consumers and their peak prey availability show non-linear relationships with climate anomaly magnitude, withmismatches exceeding 14 days associated with significant declines in reproductive success. Synthesis identifiestrait-based vulnerability predictors and a hierarchical adaptation management framework for European vertebrateconservation under projected 2050 and 2100 climate scenarios aligned with EU Habitats Directive Article 17 reportingneeds.
Keywords: EU Habitats Directive; European vertebrates; climate velocity; evolutionary adaptation; physiological stress; distributional change; phenological mismatch; range shifts; phenological shifts; climate variability